Efektifitas Penggunaan Media Pembelajaran Menara Roda untuk Memberdayakan Peserta Didik Berkebutuhan Khusus - Prayitno Prayitno (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
Students with special needs at Tunjung 1 Public Elementary School have limited social interaction, verbal and emotional communication. Need to be trained in society to be given good opportunities, through special education services. Learning facilities that attract his attention need to be created, in order to help him socialize, play together without being disturbed, and can improve his academic achievement. For this reason, the writer created the